INKUISISI GEREJA KATOLIK TERHADAP UMAT ISLAMDI SPANYOL - Nur Fitriyana Nur Fitriyana (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2016)
For Catholics, Jesus was the only legitimate way to salvation. Then the consequence of that was the creed outside the church as heretical teaching. The Inquisition was a tribunal set up by the church to investigate (inquirere from Latin), whether the statement of faith of the members in accordance with the teachings of the church. Based on historical fact, there are three kinds of Inquisition in church history, namely: 1) the Inquisition held in 1184 in southern France, to handle Catharists. 2) The Roman Inquisition that began in 1542 and 3) Spanish Inquisition that began in 1478, organized by the Spanish government to investigate the conversos ,Catholics who had been the Jewish and Muslim, or those who pretend to be Catholic. There are seventeen courts of the Inquisition in Spain and 10 heretics were burned. In the 1479 because of pressure from the authorities of the Catholic Church in Spain, Ferdinand II of Aragon and Isabella I of Castile, Pope Sixtus IV formed an independent Spanish Inquisition, led by the high council and implementing the Great Inquisition.